Effects of Weight Hourly Space Velocity and Catalyst Diameter on Performance of Hybrid Catalytic-Plasma Reactor for Biodiesel Synthesis over Sulphated Zinc Oxide Acid Catalyst - Luqman Buchori; Istadi Istadi; Purwanto Purwanto (Bulletin of Chemical Reaction Engineering & Catalysis, 2017)
Biodiesel synthesis through transesterification of soybean oil with methanol on hybrid catalytic-plasma reactor over sulphated zinc oxide (SO42-/ZnO) active acid catalyst was investigated. This research was aimed to study effects of Weight Hourly Space Velocity (WHSV) and the catalyst diameter on performance of the hybrid catalytic-plasma reactor for biodiesel synthesis. The amount (20.2 g) of active sulphated zinc oxide solid acid catalysts was loaded into discharge zone of the reactor. The WHSV and the catalyst diameter were varied between 0.89 to 1.55 min-1 and 3, 5, and 7 mm, respectively. The molar ratio of methanol to oil as reactants of 15:1 is fed to the reactor, while operating condition of the reactor was kept at reaction temperature of 65 oC and ambient pressure. The fatty acid methyl ester (FAME) component in biodiesel product was identified by Gas Chromatography - Mass Spectrometry (GC-MS). The results showed that the FAME yield decreases with increasing WHSV. It was found that the optimum FAME yield was achieved of 56.91 % at WHSV of 0.89 min-1 and catalyst diameter of 5 mm and reaction time of 1.25 min. It can be concluded that the biodiesel synthesis using the hybrid catalytic-plasma reactor system exhibited promising the FAME yield.